PERANCANGAN MEDIA PEMBELAJARAN PADA UNIVERSITAS ISLAM KUANTAN SINGINGI - Jasri oc; Harianja Harianja (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2020)
With the advancement of information and communication technology, especially in learning that is not an expert causing technological lags, so the lecturers think the teaching and learning process is more difficult, the huge cost of instructing lecturers to use teaching and learning methods is not in accordance with the times so students are bored with the lecture process. By modeling instructional media, it will be easier for lecturers of the Kuantan Singingi Islamic University to carry out the teaching and learning process, using learning media more easily, using low costs and students will not feel bored. The results of this research can be a facility for lecturers to deliver material and students become active in learning independently both at home and in campus.